The Effectiveness of KWL on Reading Expository Texts Across Reading Anxiety Levels - Luthfi Retriansyah; Francisca Maria Ivone; Sintha Tresnadewi (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This quasi-experimental research tries to find out the effectiveness of KWL on student’s comprehension of expository text and also observe how effective KWL is on the reading comprehension of the students across reading anxiety level. It is found that the difference in reading comprehension between student taught by using KWL and those taught by using conventional way is significant, the reading activities offered by KWL steps were effective to facilitate students in enhancing their comprehension in reading, and thedifference between students with low reading anxiety and those with high reading anxiety taught by using KWL is significant as well.Abstrak: Penelitian quasi-experimental ini bertujuan untuk melihat efektivitas dari pengunaan strategy KWL terhadap pemahaman siswa dalam memahami teks ekspositori dan juga untuk melihat efektivitas KWL pada pemahaman siswa dengan tingkat anxiety yang berbeda. Ditemukan bahwa ada perbedaan signifikan pada pemahaman membaca siswa antara siwa yang diajar mengunakan KWL dan siswa yang diajar secara konvensional, aktivitas membaca pada KWL sangat efektif dalam memfasilitasi siswa untuk meningkatkan pemahaman mereka dalam membaca, ditemukan juga perbedaan yang signifikan diantara siswa yang memiliki low anxiety dengan high anxiety ketika KWL diterapkan.